2017
DOI: 10.1021/acs.jpcc.7b06458
|View full text |Cite
|
Sign up to set email alerts
|

Optical Transitions and Excitonic Properties of Ge1–xSnx Alloy Quantum Dots

Abstract: Using hybrid functional calculations and experimental characterization, we analyze optical properties of 2–3 nm Ge1–x Sn x alloy quantum dots, synthesized by colloidal chemistry methods. Hybrid functional theory, tuned to yield experimental bulk band structure of germanium, reproduces directly measured properties of Ge1–x Sn x quantum dots, such as lattice constants, energy gaps, and absorption spectra. Time-dependent hybrid functional calculations yield optical absorption in good agreement with experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…To date, literature on the synthesis and characterization of Ge 1– x Sn x NCs has focused on convection heating methods to achieve a wide range of Sn compositions while controlling the particle diameter. Esteves et al, Hafiz et al, and Demchenko et al have synthesized Ge 1– x Sn x NCs with diameters less than 4 nm, demonstrating size control across a range of low compositions, 0.04 ≤ x ≤ 0.24. Ramasamy et al have demonstrated similar control for larger diameter Ge 1– x Sn x NCs with larger Sn compositions. , In this work, facile microwave heating methods are used to achieve a wide range of particle sizes, 3.8–9.3 nm in diameter, across a narrow range of Sn compositions, 0.12 ≤ x ≤ 0.18, by varying the synthesis temperature (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, literature on the synthesis and characterization of Ge 1– x Sn x NCs has focused on convection heating methods to achieve a wide range of Sn compositions while controlling the particle diameter. Esteves et al, Hafiz et al, and Demchenko et al have synthesized Ge 1– x Sn x NCs with diameters less than 4 nm, demonstrating size control across a range of low compositions, 0.04 ≤ x ≤ 0.24. Ramasamy et al have demonstrated similar control for larger diameter Ge 1– x Sn x NCs with larger Sn compositions. , In this work, facile microwave heating methods are used to achieve a wide range of particle sizes, 3.8–9.3 nm in diameter, across a narrow range of Sn compositions, 0.12 ≤ x ≤ 0.18, by varying the synthesis temperature (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Experimental band gap energies, determined using a polynomial fitting, agree well with literature values for Ge 1– x Sn x NCs in the 1–5 nm range (Figure ). ,, However, few values have been reported for Ge 1– x Sn x NCs in the 5–9 nm range. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of binary alloy QDs, the band gaps could be altered by controlling the QDs particles size and this feature of QDs is highly significant due to the quantum confinement effect, as compared to the bulk nanomaterials. [107,108] Thus, the extremely small particles size of alloy QDs make them highly effective visible light catalysts for solar photocatalysis, compared to the bulk semiconductors. Some recent reports on alloy QDs based composite photocatalysts are provided in Table 1.…”
Section: Alloy Quantum Dots Based Compositesmentioning
confidence: 99%